Bioengineered corneal tissue for minimally invasive vision restoration in advanced keratoconus in two clinical cohorts - Rafat, Mehrdad; Jabbarvand, Mahmoud; Sharma, Namrata; Xeroudaki, Maria; Tabe, Shideh; Omrani, Raha; Thangavelu, Muthukumar; Mukwaya, Anthony; Fagerholm, Per; Lennikov, Anton; Askarizadeh, Farshad; Lagali, Neil (Nature biotechnology, 2023)
Visual impairment from corneal stromal disease affects millions worldwide. We describe a cell-free engineered corneal tissue, bioengineered porcine construct, double crosslinked (BPCDX) and a minimally invasive surgical method for its implantation. In a pilot feasibility study in India and Iran (clinicaltrials.gov no. NCT04653922 ), we implanted BPCDX in 20 advanced keratoconus subjects to reshape the native corneal stroma without removing existing tissue or using sutures. During 24 months of follow-up, no adverse event was observed. We document improvements in corneal thickness (mean increase of 209 ± 18 µm in India, 285 ± 99 µm in Iran), maximum keratometry (mean decrease of 13.9 ± 7.9 D in India and 11.2 ± 8.9 D in Iran) and visual acuity (to a mean contact-lens-corrected acuity of 20/26 in India and spectacle-corrected acuity of 20/58 in Iran). Fourteen of 14 initially blind subjects had a final mean best-corrected vision (spectacle or contact lens) of 20/36 and restored tolerance to contact lens wear. This work demonstrates restoration of vision using an approach that is potentially equally effective, safer, simpler and more broadly available than donor cornea transplantation. A bioengineered cornea made of collagen restores vision in a pilot clinical study.